Trends in testicular germ cell tumors among native black African men do not mirror those of African Americans: multi-institutional data from South Africa - Farzana Cassim; Amy Pearlman; Ethan Matz; Ryan Terlecki; Andre van der Merwe; John Lazarus; Cecelia Lloyd; Bhavish Kowlessur (African Journal of Urology, 2021)
Abstract Background Testicular germ cell tumor (TGCT) is most frequently diagnosed in young males and its etiology remains poorly understood. Cases of newly diagnosed TGCT have been rising in the United States and incidence among African Americans (AA) has increased nearly 40%. Incidence of TGCT in native black African (BA) males, conversely, has remained low. We sought to determine the racial identification of patients diagnosed with TGCT in Cape Town, South Africa. We hypothesize that the rise in TGCT among AA males is distinct from that of BA males in South Africa. Methods A retrospective review involving two tertiary care centres in the Western Cape was performed. Data were extracted for males > 13 years of age diagnosed with TGCT from January 1, 2000 to June 30, 2015. Racial status was self-declared and included BA, Caucasian, Mixed Ancestry (MA), and Asian. Patients were identified from combined Urology–Oncology clinic logs at both institutions, as well as from pathology records at the National Health Laboratory Service indicating any form of testicular cancer. Results 225 patients were identified. 97% of cases involved males identified as MA (130) or Caucasian (88). Only 2% of the study population identified as BA, with complete absence of self-identifying BA males for several years within the queried interval. Among males diagnosed with TGCT, the percentage self-identifying as Caucasian increased over time (R 2 0.92). Conclusions Males diagnosed with TGCT in the Western Cape predominantly self-identify as MA or Caucasian. Exceedingly few cases are attributed to BA, and even less to Asian males. The trend in racial distribution suggests that the increasing incidence reported for AAs may be due to interracial gene exchange, environmental factors, or a combination thereof.